Proceedings of the First International Conference on Administration Science (ICAS 2019) 2019
DOI: 10.2991/icas-19.2019.41
|View full text |Cite
|
Sign up to set email alerts
|

Module Achievement of 1st Piano Minor Learning Standard Competence Based on Multimedia at the Jakarta Institute of Art

Abstract: The aim of this study was to produce a learning module with video for equality the student competence. A module is an effective tool for individual learning. Completing the module with video is the multimedia way that performs the text, picture, sound, and animation that make the learning more interesting, easy and efficient. Piano learning is practical individual learning. Many of the piano's method teaching is being developed in order to make the student's interest and easy to learn than can play piano immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Hal ini dimungkinkan karena mereka kekurangan waktu yang cukup untuk berlatih, sehingga penguasaan motorik tidak maksimal. Namun bahan ajar lain seperti membaca notasi, posisi tubuh, menggunakan piano dan ekspresinya cukup menguasai (Kusumaningsih et al, 2019).…”
Section: Pendahuluanunclassified
“…Hal ini dimungkinkan karena mereka kekurangan waktu yang cukup untuk berlatih, sehingga penguasaan motorik tidak maksimal. Namun bahan ajar lain seperti membaca notasi, posisi tubuh, menggunakan piano dan ekspresinya cukup menguasai (Kusumaningsih et al, 2019).…”
Section: Pendahuluanunclassified
“…In research (Nasir & Bargstädt, 2017) found that video tutorials not only transfer knowledge to the audience but also motivate them to learn. Modules equipped with videos will be more effective, efficient, attractive and productive in providing positive learning (Kusumaningsih, Nadiroh, & Ibrahim, 2019). Learning by watching videos has become the dominant millennial way of learning.…”
Section: Introductionmentioning
confidence: 99%